Effects of Three Essential Oil Fumigation Treatments on the Postharvest Control of Botrytis cinerea and Their Efficacy as Preservatives of Cherry Tomatoes - Jiang, Lin-Lin (Plant disease, 2023)
Cherry tomatoes (Solanum lycopersicum) are becoming increasingly popular due to their nutrition and delicious flavor. However, cherry tomatoes are highly perishable and susceptible to various pathogenic microorganisms after harvest, such as Botrytis cinerea. In the pretest experiment, we screened out three kinds of plant essential oils (EOs) (Torreya grandis oil, Eriobotrya japonica oil, and Citrus medica oil) that have strong fungicidal activity on B. cinerea from cherry tomatoes. To further evaluate the postharvest preservation application prospect of these three oils for cherry tomatoes, the oils were extracted from different parts of three plants by hydrodistillation, and their chemical constituents were analyzed by gas chromatography-mass spectrometry. The main representative components of T. grandis oil, E. japonica oil, and C. medica oil were δ-cadinene (11.76%), transnerolidol (9.70%), and 5,7-dimethoxycoumarin (23.22%), respectively. These three EOs effectively inhibited the mycelial growth of B. cinerea in vitro, with EC50 values of 81.672, 144.046, and 221.500 μl/liter, respectively. Compared with the blank control and other oil treatments, the T. grandis oil (at a concentration of 200 µl/liter) fumigation treatment was more effective at inhibiting the growth rate of the pathogen. In addition, the phenolic content and phenylalanine ammonia lyase, β-1,3-glucanase, chitinase, and peroxidase activities of tomatoes significantly increased on the seventh day due to the T. grandis oil treatment. The present study shows that these three oils with high extraction rates have preservation potential for cherry tomatoes. Among these three EOs, T. grandis oil can be used to further develop preservative products as a fumigant